Reptiles from Late Cretaceous coastal environments of northern Patagonia - Brandoni de Gasparini, Zulma Nélida (2001)
Toward the end of the Cretaceous the Atlantic Ocean covered parts of central-western Patagonia forming a wide archipelago. Remains of terrestrial and marine reptiles have been recorded in the Campanian and Maastrichtian of this area in rocks that represent coastal or marginal marine environments. These taphocenoses are especially interesting because they include taxa not only of different environmentals requirements, but also of different biogeographical backgrounds. The presence of a wide archipelago is a plausible explanation of the association recorder, such as plesiosaurs with continental chelids, boids and dinosaurs (e.g., La Colonia, Chubut; Ranquil-Co, Mendoza), or plesiosaurs and mosasaurs with chelids (e.g., Lui-Malal, Mendoza). From a paleobiogeographic point of view, some taxa have mainly south Gondwanan distribution (chelids, meiolanids, the plesiosaur Aristonectes Cabrera), others taxa are related to North American taxa (the plesiosaur Sulcusuchus Gasparini and Spallletti, hadrosaurid dinosaurs); and still others were cosmopolitan toward the end of the Mesozoic (elasmosaurids and mosasaurines).